The Biosecuritization of the Tourist City: Some Reflections from and about Lisbon Nightlife - Nofre, Jordi; Garcia-Ruiz, Manuel; Martins, João Carlos (ACME, 2023)
The impact of COVID-19 on tourism has been enormous across the globe. The successful recovery of the tourism industry at the local, national, and global levels is strictly dependent on the efficient contention and mitigation of the COVID-19 pandemic at the global level and on the capacity of tour operators, governments, and other actors to generate complete trust among tourists. In this article, we examine the biosecuritization of Lisbon (Portugal) and the efforts carried out by the administration to preserve the city as a COVID-free urban destination. In this sense, we will examine two main strategies that have received little attention from the scholarly community, namely (i) the strengthening of repressive, punitive, and criminalizing policies against suburban working-class youths ('the perilous') within the scope of guaranteeing a COVID-free city for tourists ('the untouchables'), and (ii) the (in)governance of the urban night of Lisbon during the current pandemic. In the last section, we will argue how mobility restrictions, lockdowns, and nighttime curfews have shown us how central culture, arts, entertainment, and leisure are for not only the cultural and social life of many young and adult people in Europe but also for their socio-emotional wellbeing.